Improving Needle Visualization by Novice Residents During an In‐Plane Ultrasound Nerve Block Simulation Using an In‐Plane Multiangle Needle Guide. Issue 10 (11th June 2013) - Gupta, Rajnish K.; Lane, Jason; Allen, Brian; Shi, Yaping; Schildcrout, Jonathan S.
Abstract Objective Ultrasound‐guided regional anesthesia with in‐plane needle approaches can be challenging due to difficult needle visualization. We hypothesized that an in‐plane, multiangle needle guide can help reduce the time it takes novice regional anesthesiologists to perform a simulated ultrasound‐guided nerve‐targeting procedure and enhance the visualization of the needle. Design Crossover simulation study. Setting Simulation environment at an academic institution. Subjects Volunteer trainees in their postgraduate years 1 and 2. Methods Sixteen subjects were randomized to repeat a single nerve targeting simulation task four times with and four times without a needle guide. End points were time to complete the nerve targeting, needle visualization, number of passes, and needle approximation to the target. Results The needle guide reduced median time to complete the task by 27% (95% confidence interval: 4–44%) and increased the odds of an acceptable needle visualization by 355% (95% confidence interval: 171–737%). A learning benefit for the time outcome was also noted, with multiple attempts regardless of whether the needle guide was used or not. Conclusions A needle guide can help reduce the time needed to complete a simulated nerve targeting procedure and enhance needle visualization for the novice sonographer in a phantom gel simulation. There was no significant reduction in the number of needle passes or in improvement of target approximation noted.